Discount Programs And Special Offers For Consumer Purchasing Decisions Of H&M Products - Ghinaa Putri Adizka; Syafna Hanifa Iskandar; Adistria Putri; Mohamad Zein Saleh (Pusat Riset dan Inovasi Nasional, 2024)
H&M (Hennes & Mauritz AB) is one of the leading global retail brands known for its trendy and affordable clothing collections. This research aims to analyze the marketing strategies used by H&M and their impact on the brand's success as a major player in the global clothing industry. In an era of intense competition in the retail industry, discount programs and special offers have become a common strategy used by brands like H&M to attract consumer attention and increase sales. The impact of strategic discounts on consumer behavior and business performance, focusing on the case example of leading retail company H&M. Additionally, this research identifies factors that can influence the success or failure of a strategy, including economic context, perceived value, and customer segmentation. The research method used in this research is a survey via questionnaire given to a sample of H&M consumers in the Bintaro area. The results of this research provide in-depth insight into the role of discounts in the context of the clothing industry and provide guidance for retail companies, especially H&M, in designing effective discount strategies to increase customer satisfaction and financial results.